2018
DOI: 10.1016/j.jaci.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen cleavage products and Toll-like receptor 4 promote the generation of programmed cell death 1 ligand 2–positive dendritic cells in allergic asthma

Abstract: Our findings unveil the "protease-FCP-TLR4-mast cell-IL-13" axis as a molecular mechanism for generation of T2-favorable PD-L2 DCs in allergic asthma and suggest that targeting the PD-L2 DC pathway might be effective in suppressing allergic T-cell responses in the airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…Another mouse model study identified a potential pathway linking protease allergen exposure to airway programmed cell death ligand 2 (PD-L2) expressing T H 2-skewing dendritic cells. 63 This novel pathway was based on protease-induced fibrinogen cleavage products acting on mast cells, leading to release of IL-13, which skewed the dendritic cells to become ''T H 2-favorable PD-L2 1 '' cells. Whether this pathway is operative in human subjects remains to be determined.…”
Section: Risk Of Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…Another mouse model study identified a potential pathway linking protease allergen exposure to airway programmed cell death ligand 2 (PD-L2) expressing T H 2-skewing dendritic cells. 63 This novel pathway was based on protease-induced fibrinogen cleavage products acting on mast cells, leading to release of IL-13, which skewed the dendritic cells to become ''T H 2-favorable PD-L2 1 '' cells. Whether this pathway is operative in human subjects remains to be determined.…”
Section: Risk Of Asthmamentioning
confidence: 99%
“…In particular, the interconnectedness between the microbiome and the risk of development of asthma (and wheeze) was a prominent feature of these studies, as was the identification of cellular stress (and in particular ORMDL3) as a mechanism for asthma development. 4,5,15,63,64 Nonetheless, all of the investigations discussed have greatly expanded our knowledge base, and the future will tell whether these findings lead to novel therapies and/or better targeting of our therapies to specific patient populations.…”
Section: Biomarker Discovery In Asthmatic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrinogen had an Mo-DC maturation effect comparable with poly I:C, TNF-α, and PGE 2 , but it failed to induce IL-12 production ( 118 ). On the other hand, it has been recently reported that fibrinogen cleavage products generated by protease allergens, through induction of IL-13 production by mast cells, increased the number of T H 2-favorable (PD-L2 + ) DCs in allergic asthma ( 119 ). Interestingly, another member of the fibrinogen-related protein superfamily, soluble fibroleukin or fibrinogen-like protein 2 (sFGL2), highly inducible by IFN-γ and with features of APP, has a 50 kDa weight and is highly expressed in cytotoxic T cells and Tregs upon activation ( 120 ).…”
Section: Tolerogenic Actions Of Apps On Dcsmentioning
confidence: 99%
“…Furthermore, thrombin, the classic activator of coagulation, can also cleave fibrinogen into FCPs resulting in further upregulation of the TLR4 pathway. A recent study identifies a programmed cell death 1 ligand 2 + (PD-L2 + ) DC phenotype which accounts for the induction of Th2 cell response upon protease allergens exposure and fibrinogen-cleavage products can promote the generation of PD-L2 + DC through TLR4 (Cho M. et al, 2017 ). These studies suggest that TLR4 plays a critical role in the allergic response upon exposure to exogenous proteases.…”
Section: Introductionmentioning
confidence: 99%